Optical characterization of graphene multi-layers on SiO2 - López Loaiza, Xavier Alexander (2022)
Graphene is a revolutionary material that brought numerous modern applications in many fields of industry. Addi- tionally, it presents some properties that enable its use in many electronic devices. As a consequence, the control of the properties, which varies depending on its synthesis, is considered an important factor in its efficiency. For this purpose, the characterization of this material is extremely important because between all the features we can obtain, the number of layers is going to dictate a few principal properties over the material. Thus, in order to identify the number of layers of a graphene flake, it is necessary to apply two main techniques. In general, there are several characterization methods that can help us to complete this task, however, we are going to use and implement two of them. These techniques are optical contrast analysis and Raman spectroscopy. Although the optical contrast analysis is considered the simplest technique to determine the number of layers of 2D materials, it is very easy to use due to the employment of free software (ImageJ) accompanied with good results. On the other hand, Raman spectroscopy could be hard to implement, which cannot differentiate between two or more layers present in the material and uses complicated laboratory equipment. Nevertheless, Raman spectroscopy is going to be utilized in this work to complement the results obtained from the optical contrast analysis. The main objective of this work is to be able to identify the number of layers using the method of optical contrast analysis that can be reproducible in every computer due to the open software it uses. Therefore, this work will contribute to the determination of the number of layers for any 2D material making the use of a simple method presented here.